Effect of different dietary lipid levels on the reproduction of Rhamdia quelen (Quoy and Gaimard, 1824). (28th August 2013) - Coldebella, I. J.; Emanuelli, T.; Veiverberg, C. A.; Pretto, A.; Rossato, S.; Ferreira, D.; Barcellos, L. J. G.; Neto, J. Radünz
Abstract: Lipids include some of the most important nutrients that affect the survival and growth of fishes in their early life stages. Lipid deficiency prior to spawning may significantly reduce egg production, hatchability and the number of surviving larvae. In this study, we investigated the effects of isocaloric diets containing 80, 140 and 200 g kg −1 of lipids (lipid source, soy oil) for 90 days. The following data were collected at 0, 45 and 90 days: final weight; length; conditioning factor; hepatosomatic, gonadosomatic and visceral fat indices; total plasma protein; testosterone; 17ß‐estradiol; free amino acids; and ovary and muscle fatty acid profiles. Additionally, fecundity, oocyte production, egg morphometric parameters, and larval and postlarval growth were evaluated. Results were not statistically different for husbandry and biochemical parameters, but visceral fat content increased with increase in dietary lipid levels. The fatty acid profiles and composition differed among dietary treatments. The egg diameter and area were significantly low in fish fed the 200 g kg −1 lipid diet, thereby hindering growth, survival and weight compared to those in postlarval fish ( P  < 0.05). The best reproductive rates were obtained when using diets containing 80–140 g kg −1 total lipids.